HL7 in Personal Health System component’s integration for Mental Health Treatment - Robles, Juan Carlos Castro; Domingo, Albert; Colomé, Josep Maria; Estevez, Soraya (Journal of Health Informatics, 2011)
Help4Mood is a project inside 7th European Framework Programme (FP7) for developing a computational distributed system to support remotely the treatment of patients with major depression at home. Core components are integrated with Health Level Seven (HL7) standard. One of the main goals of this system is to use the paradigm of a Virtual Agent to support the first symptoms of clinician alert of a patient, to interact with him an to prevent some causes of relapse. The system processes inputs from different devices (to monitor sleeping, eating and motor activity) in a decision support system, and the Virtual Agent interacts with the patient before clinical support from hospital is needed. The technical framework is using the open source HL7-standard-based healthcare integration engine, Mirth Connect, to interact with the different subsystems, analyze data and give different priorities for messages in queues. Particularly, the use of standard HL7 will contribute to interest in the project results and the potential impact through the development, dissemination and use, as stated in the analysis of the European commission